The Formation and Significance of Ethical Thought in Chinese Huai Opera - Xu, Wenya (International Journal of Social Sciences and Public Administration, 2024)
This paper explored the background and profound significance of ethical thought in Chinese Huai Opera. Its formation is based on the unique regional culture and profound historical traditions, while also deeply influenced by social changes and the needs of the people. Drawing on the essence of Confucianism, Taoism, Buddhism, and other diverse ideologies, the ethical thought in Huai Opera serves multiple social functions such as entertainment, cognition, and aesthetics. This study aimed to reveal the cultural and social value of ethical thought in Huai Opera and provide theoretical support for the inheritance and development of Huai Opera.